Boundedness of Some Singular Integral Operators on Morrey-Herz Spaces over Locally Compact Vilenkin Groups (Communications in Mathematical Research, 2021)
In this paper the boundedness results for some fractional and singular integral operators on the homogeneous Morrey-Herz spaces over locally compactVilenkin groups are shown.
Keywords: Vilenkin group; Morrey-Herz space; singular integral; fractional integral.